A feasibility study of low‐dose ketamine for acute management of suicidal ideation. Issue 4 (15th August 2022) - Gaither, Rachel; Ranney, Megan; Peachey, Alyssa; Burock, Jeffrey; Rogers, Jyllian; Bucci, Lindsey; Beaudoin, Francesca L.
Abstract: Objective: Mood disorders complicated by suicidal ideation (SI) frequently present to the emergency department (ED) for care. Currently, patients with SI in the ED do not typically receive targeted interventions. Ketamine may have a role in treating SI within the ED because subanesthetic doses have rapid‐acting antidepressant and antisuicidal properties. Methods: This single‐arm, open‐label feasibility study enrolled 14 participants from the ED with acute SI who were awaiting voluntary admission to inpatient psychiatry to receive ketamine at 0.5 mg/kg, administered intravenously. Participants were assessed post administration to evaluate feasibility of administration in the ED and short‐term effectiveness. Feasibility was determined by acceptability by patients and physicians as well as tolerability and ability to recruit participants into the study. Efficacy was assessed based on changes in (1) self‐reported mood and (2) suicidal ideation pre‐ and postinfusion of ketamine. Results: All patients reported severe depression and active SI at baseline. No serious adverse events were reported, and acceptability was rated highly by both participants and physicians (>70%). Two hours after receiving ketamine 0.5 mg/kg, the mean SI and somatic symptom burden were decreased compared to baseline ( P  < 0.001 and P  = 0.005, respectively), and the mean self‐reported mood was increased ( P  = 0.006). Improvements in mood and decreases in suicidality persisted at 6 hours. Conclusions: Overall, ketamine was well tolerated, considered feasible by both participants and physicians, and demonstrated short‐term efficacy. There is a growing body of evidence demonstrating the feasibility of ketamine administration in the ED, and larger randomized trials should be conducted to establish treatment recommendations for patients with SI in the ED.